Associations Between the Use of Renin–Angiotensin System Inhibitors and the Risks of Severe COVID-19 and Mortality in COVID-19 Patients With Hypertension: A Meta-Analysis of Observational Studies - Dai, Xiao-Ce; An, Zhuo-Yu; Wang, Zi-Yang; Wang, Zi-Zhen; Wang, Yi-Ren (Frontiers in Cardiovascular Medicine, 2021)
Aim Angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) share their target receptor site with the SARS-CoV-2 virus, that may cause angiotensin-converting enzyme-2 (ACE2) receptor up-regulation which facilitates contagious coronavirus disease (COVID-19) entry into cells, there is concern that ACEI/ARB could increase the risk of developing a severe and fatal form of COVID-19. The impact of discontinuing these drugs in patients with COVID-19 remains uncertain. We aimed to assess the association between the use of ACEI/ARB and the risk of death and severity in patients with COVID-19. Method A systematic search of PubMed, EMBASE, Cochrane and MedRxiv.org through December 1, 2019 to June 20, 2020 was performed. We also identified additional citations through hand-searching of reference lists. Findings Forty-two observational studies comprising 63,893 participants were included. We found that ACEI/ARB the use of ACEI/ARB was not significantly associated with reduction in the relative risk of all-cause mortality compared to controls (OR: 0.87, 95% confidence interval [95% CI]: 0.75 – 1.00; I2=57%, p=0.05). We found no significant reduction of disease severity in the ACEI subgroup (OR: 0.95, 95% CI: 0.88 – 1.02, I2=50%, p=0.18) or in the ARB subgroup (OR: 1.03, 95% CI: 0.94 – 1.13, I2=62%, p=0.48) or in the ACEI/ARB subgroup (OR: 0.83, 95% CI: 0.65 – 1.08, I2=67%, p=0.16). Moreover, seven included studies showed no significant difference between the duration of hospitalization between the two groups (mean difference: 0.33, 95% CI: −1.75 to 2.40, p=0.76). Conclusion ACEI/ARB might have no significant effect on the mortality, disease severity or duration of hospitalization in COVID-19. On the basis of the findings from this meta-analysis, no indication exists to prophylactically stop ACEI or ARB treatment because of concerns about COVID-19.